Supervision and Computerized Neurocognitive Baseline Test Performance in High School Athletes: An Initial Investigation - Kuhn, Andrew Warren (J Athl Train, 2014)
CONTEXT: Computerized neuropsychological testing batteries have provided a time-efficient and cost-efficient way to assess and manage the neurocognitive aspects of patients with sport-related concussion. These tests are straightforward and mostly self-guided, reducing the degree of clinician involvement required by traditional clinical neuropsychological paper-and-pencil tests. OBJECTIVE: To determine if self-reported supervision status affected computerized neurocognitive baseline test performance in high school athletes. DESIGN: Retrospective cohort study. SETTINGS: Supervised testing took place in high school computer libraries or sports medicine clinics. Unsupervised testing took place at the participant's home or another location with computer access. PATIENTS OR OTHER PARTICIPANTS: From 2007 to 2012, high school athletes across middle Tennessee (n = 3771) completed computerized neurocognitive baseline testing (Immediate Post-Concussion Assessment and Cognitive Testing [ImPACT]). They reported taking the test either supervised by a sports medicine professional or unsupervised. These athletes (n = 2140) were subjected to inclusion and exclusion criteria and then matched based on age, sex, and number of prior concussions. MAIN OUTCOME MEASURE(S): We extracted demographic and performance-based data from each de-identified baseline testing record. Paired t tests were performed between the self-reported supervised and unsupervised groups, comparing the following ImPACT baseline composite scores: verbal memory, visual memory, visual motor (processing) speed, reaction time, impulse control, and total symptom score. For differences that reached P < .05, the Cohen d was calculated to measure the effect size. Lastly, a χ(2) analysis was conducted to compare the rate of invalid baseline testing between the groups. All statistical tests were performed at the 95% confidence interval level. RESULTS: Self-reported supervised athletes demonstrated better visual motor (processing) speed (P = .004; 95% confidence interval [0.28, 1.52]; d = 0.12) and faster reaction time (P < .001; 95% confidence interval [−0.026, −0.014]; d = 0.21) composite scores than self-reported unsupervised athletes. CONCLUSIONS: Speed-based tasks were most affected by self-reported supervision status, although the effect sizes were relatively small. These data lend credence to the hypothesis that supervision status may be a factor in the evaluation of ImPACT baseline test scores.